Omnidirectional excitation of surface waves and super-Klein tunneling at the interface between two different bi-isotropic media - Kim, Seulong; Kim, Kihong (Physical Review B, 2020)
We study theoretically some unique characteristics of surface electromagnetic waves excited at the interface between two different kinds of general bi-isotropic media, which include Tellegen media and chiral media as special cases. We derive an analytical dispersion relation for those waves, using which we deduce eight different conditions under which they are generated between two Tellegen media and between two chiral media independently of the component of the wave vector along the interface. These make it possible to excite the surface waves for all or a wide range of incident angles in attenuated total reflection experiments on multilayer structures. We generalize the concept of a conjugate matched pair to bi-isotropic media and obtain several conditions under which the omnidirectional total transmission, which we call the super-Klein tunneling, occurs through conjugate matched pairs consisting of Tellegen media and of chiral media. We find that these conditions are closely linked to those for the omnidirectional excitation of surface waves. Using the invariant imbedding method, we perform extensive numerical calculations of the absorptance, the transmittance, and the spatial distribution of the electromagnetic fields for circularly polarized waves incident on bilayer structures and confirm that the results agree perfectly with the analytical predictions.
Keywords: Analytical predictions; Attenuated total reflections; Circularly polarized waves; Dispersion relations; Distribution of the electromagnetic field; Multilayer structures; Numerical calculation; Surface electromagnetic waves